ANALISIS RISIKO DAN RENTABILITAS PEMBIAYAAN TANPA BUNGA PADA AGROINDUSTRI TAPIOKA - Kiki Yulianto; Sukardi Sukardi; Nastiti Siswi Indrasti; Sapta Raharja (AGROINTEK, 2021)
Financing risk is a condition of uncertainty that affects the success of a business to gain profit. Meanwhile, profitability is the ability to generate profits based on the capital owned. This study aims to analyze the risk and profitability of financing in the tapioca agro- industry using an interest-free calculation basis. The data used are primary data from field observations at the center of tapioca agro-industry in Ciluar, Bogor Regency, and secondary data from literature studies. The analysis is carried out by calculating the risk of loss and profitability of financing using the assumption of an acceptance rate of 10% of the total capital and when the level of acceptance falls -10% of the total capital owned. Furthermore, a comparison is made between tapioca agro-industries that use an interest-bearing financing scheme and an interest-free financing scheme which includes variables of risk of loss, income level, and profitability level. The research results prove that the bigger the loan used, the greater the risk to be borne. Another finding, interest-free financing in the tapioca agro- industry has a higher rate of return and income than interest-bearing financing